The Relationship Of Formula Milk Promotion With The Failure Of Exclusive Breast Milk At Posyandu Dahlia Babelan Bekasi - Salamah Tomasita Batu; Yusrini; Elza Siti Rizkiyah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
According to WHO and UNICEF (2013) worldwide only 39% of children under six months get exclusive breastfeeding. The failure of exclusive breastfeeding is influenced by various factors, one of which is the incessant promotion and advertisement of formula milk which has an influence on mothers to be interested in buying it, especially for mothers with low knowledge and education. The aim of the study was to determine the relationship between formula milk promotion and the failure of exclusive breastfeeding. This research uses associative descriptive method using accidental sampling technique with 53 respondents. The results showed that there was a relationship between the failure of exclusive breastfeeding and the promotion of formula milk, it can be seen that the failure rate of exclusive breastfeeding was 83.0% and the promotion of formula milk was high as much as 77.4% with P value = 0.031 (< 0.05), which means there is a the relationship between the promotion of formula milk with the failure of exclusive breastfeeding. Suggestions for increasing the promotion of exclusive breastfeeding in health care settings. Keywords: Promotion of Formula Milk, Exclusive Breastfeeding, Breastfeeding Failure Factors